Analisis Siphon Cimanuk Daerah Irigasi Leuwigoong Kabupaten Garut - Sulwan Permana; Muthi’ah Hudaedi (Institut Teknologi Garut, 2025)
The Cimanuk Siphon is one of the cross-drainage structures built to convey discharge from an irrigation channel whose path is interrupted by a long-span valley or a river. To date, the Cimanuk Siphon has not yet been operated because its construction has not been completed. The success of an irrigation system can be assessed through the performance of its channels and structures in operation. Therefore, an analysis of irrigation system management and infrastructure is required to optimize water availability and the performance of irrigation channels. This study aims to determine the adequacy of water availability in the upper reaches of the Cimanuk River for distribution to agricultural land, as well as to determine the discharge flowing through the Cimanuk Siphon based on hydraulic calculations, ensuring optimal and efficient water flow. The study was conducted in Cipicung Village, Banyuresmi District, Garut Regency. The Copong Weir, which is a vertical movable weir, functions to irrigate the Leuwigoong Irrigation Area covering 5,313 ha, with a maximum dependable river discharge of 24.47 m³/s, calculated using the NRECA method. The highest evapotranspiration value was recorded in September, reaching 4.21 mm/day, based on the Penman–Monteith method. The maximum net water requirement for rice fields was 1.79 L/s, indicating that water availability from the upper Cimanuk River can meet the irrigation needs of the Leuwigoong area. The maximum discharge flowing through the Cimanuk Siphon was 5,268.34 L/s. The flow velocity at the inlet of the siphon was 0.66 m/s with a total inflow discharge of 5.27 m³/s, while at the outlet, the velocity reached 1.66 m/s with an outflow discharge of 3.52 m³/s. The total energy loss in the siphon was calculated to be 0.39 m. These findings are expected to serve as a basis for evaluating and optimizing the performance of the Cimanuk–Leuwigoong irrigation system to support sustainable water distribution for agricultural purposes.